Analisis Sekuritisasi Presiden Donald Trump Dalam Kebijakan Protecting The Nation From Foreign Terrorist Entry Into The United States (2016-2019) - Marsanda Aulia; Hermini Susiatiningsih; Satwika Paramasatya (Journal of International Relations Diponegoro, 2022)
In responding to the issue of immigrants, the United States has come up with a controversial policy. Donald Trump brought up the Protecting The Nation From Foreign Terrorist Entry Into The United States policy to limit the entry of Muslim immigrants into the United States. Donald Trump securitizes the issue by giving a speech act that forms a threat construction in the issue of Muslim immigrants. Until finally the policy that was rejected was accepted by the community and enforced. It is interesting to study how state leaders shape the construction of an issue so that they can get support from the community. This study will reveal this through a key question regarding "How does Donald Trump securitize the issue of immigrants through speech acts in the policy of Protecting the Nation from Foreign Terrorist Entry into the United States?". The purpose of this study is to explain the role of Donald Trump as a political elite in conducting securitization through speech acts in the policy of Protecting the Nation from Foreign Terrorist Entry into the United States. This research uses the type of explanatory research. In preparing the argument, the researcher uses securitization theory about how an issue phenomenon is interpreted as a threat to the state by the political elite. This study analyzes Donald Trump's statements regarding the issue of Muslim migrants. This study argues that Donald Trump plays a role in the securitization of immigrant issues so as to shape the perception of immigrants as a threat.